Farmers and farmworkers in the global apple value chain - Ntikinca, Kanyiso Lungani (Rhodes University, 2026)
This study uses the case of selected commercial apple farmers and farm workers from the Langkloof Valley to determine whether a profit-driven trading arrangement, such as a global apple value chain, can produce inclusive developmental outcomes. Mainstream global commodity chain (GCC) and global value chain (GVC) discourse, which is mainly inspired by a neoliberal approach to development, presents global chains (GCs) as ideal conduits for facilitating economic and social upgrading for suppliers/producers and their employees from developing countries such as South Africa. Economic upgrading in GCs takes place when a firm improves its processes, product offerings, functions and trade relations along a given value chain. Social upgrading in GCs, by contrast, is underpinned by the International Labour Organization’s (ILO) Decent Work Agenda, which rests on four key pillars: employment creation, rights at work, social security and social dialogue. Global production network (GPN) scholars argue that GCs produce inequality and various forms of exploitation rather than inclusive economic and social upgrading for participants. Conversely, most GCC and GVC scholars narrowly attribute these negative outcomes in GCs to governance deficits and do not pay much attention to the vertical and horizontal profit maximization activities that induce these outcomes in GCs. Nevertheless, in this study, the GCC, GVC and GPN theories are collectively referred to as the global chain framework (GCF). The GCF primarily focuses on the sphere of trade exchange and is limited in its analysis of the spheres of production and social reproduction in GCs; hence, the addition of labour process theory (LPT) and the sustainable livelihoods approach (SLA) to the theoretical framework that informs this study. In this study, the combination of the GCF, LPT and SLA is termed a ‘trilogy theoretical framework’, which covers the three spheres mentioned above. This study is not solely concerned with the surface outcomes of the selected commercial apple farmers and farm workers in the global apple value chain (as is the case in many GC studies), but it explores the underlying mechanisms that connect these three spheres and produce visible outcomes. It is for this reason that the study is grounded in a critical realist ontology, which perceives empirical or tangible observations as only a small component (tip of the iceberg) of a deeper reality that is mostly hidden. For instance, Marx (1976) argues that to understand the capitalist production of value, one must descend into the ‘hidden abode of production’, where surplus value is extracted. Suwandi (2020) notes that in GCs, the extraction of surplus value materializes across different spheres; hence, this study analyses the interaction in the spheres of production, exchange and reproduction in the global apple value chain. The GCF was founded by Marxist-inspired dependency and world systems scholars, whilst Marx pioneered the LPT. The SLA is not Marxist-inspired; however, it is ideal for analysing the sphere of social reproduction, which Marx (1976) acknowledged as an integral part of capitalist production. This study adopted a qualitative research approach to sampling (using purposive and snowball sampling), data collection (using one-on-one interviews, group interviews, observation and document analysis) and data analysis data through deductive thematic analysis. The findings in this study show that outcomes for the research participants were determined by their positionality and economic class within the global apple value chain. All the selected commercial apple farmers in this study experienced varying degrees of economic upgrading, which were largely determined by their strategic partnerships and access to other forms of capital (following the SLA definition of capital). The land reform beneficiaries in this study experienced economic upgrading through their reliance on the resources of the more established white commercial apple farmers in the Langkloof Valley. This study shows, however, that inadequate support from the state to land reform beneficiaries indirectly pushes them into unequal “new age sharecropping” type arrangements with their white ‘business partners’ and mentors. Land reform in the apple industry (especially on the selected commercial apple farms) in the Langkloof Valley is mostly decorative because it has not threatened the racially skewed land ownership patterns and economic dominance of white commercial apple farmers in the region. Instead, the white commercial apple farmers use the cheap apples that they purchase from the land reform beneficiaries to absorb the cost pressures from global supermarkets in the global apple value chain. This study also shows that a small group of mostly permanently employed (black or coloured) male farm workers experienced social upgrading, whilst the majority of the mostly seasonally employed (black or coloured) female farm workers experienced social downgrading on the selected commercial apple farms that participate in the global apple value chain. The ‘hidden abode’ of vertical and horizontal profit maximization (or surplus extraction) strategies in the global apple value chain induced rampant non-compliance (on the selected apple farms), governance deficits (from the public, private and social stakeholders) and large-scale exploitation of most of the farm workers who participated in this study. Interestingly, this study also shows that the low wages of farm workers (regardless of employment status) forced most of them to rely on alternative forms of capital to sustain their livelihoods. This study, therefore, indicates that a capitalist-driven trading arrangement such as the global apple value chain did not produce inclusive outcomes for the selected commercial apple farmers and farm workers from the Langkloof Valley.
a study of selected commercial apple farms in the Langkloof Valley of the Eastern Cape, 2018-2022
Keywords: Uncatalogued